3n-5=6n+13

Simple and best practice solution for 3n-5=6n+13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3n-5=6n+13 equation:


Simplifying
3n + -5 = 6n + 13

Reorder the terms:
-5 + 3n = 6n + 13

Reorder the terms:
-5 + 3n = 13 + 6n

Solving
-5 + 3n = 13 + 6n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-6n' to each side of the equation.
-5 + 3n + -6n = 13 + 6n + -6n

Combine like terms: 3n + -6n = -3n
-5 + -3n = 13 + 6n + -6n

Combine like terms: 6n + -6n = 0
-5 + -3n = 13 + 0
-5 + -3n = 13

Add '5' to each side of the equation.
-5 + 5 + -3n = 13 + 5

Combine like terms: -5 + 5 = 0
0 + -3n = 13 + 5
-3n = 13 + 5

Combine like terms: 13 + 5 = 18
-3n = 18

Divide each side by '-3'.
n = -6

Simplifying
n = -6

See similar equations:

| 1x+6=19 | | 4x-2x+x=-2+2x | | 3/3=w-1/6 | | (a+b)/2=0 | | 8k^3+24k=0 | | 10x-8-3-4x=6x | | 2x^4+mx^3-(m^2+5)x^2+mx+2=0 | | m-9--13 | | -3x^2-11x+70=0 | | 64×w=5568 | | y-2.1=-3.5 | | 9x-15=7x+77 | | 0=y-(-14)-(3y) | | y=-3/24-2 | | 11x-3=8x+2 | | -2/4*3/4= | | 14x^2-27x+9 | | xy^3-2x^2y^2+x^4-1 | | 2x+35=90 | | 5x-7-2 | | 35n=70000 | | xy^3-2x^2y^2+x^4-1=0 | | 3.5=-5b | | 2x-3=-9-5x | | (6y-5)w-200=e | | 5x^2=2(7x+12) | | 2p=60-4q | | -3.2=-0.8k | | 56=-7(-3+5x) | | 2/7(x)-13/5 | | X/3+7=I | | 96=3pix |

Equations solver categories